Lulusan Pendidikan Vokasi dan Probabilitas Bekerja di Sektor Intensitas Digital Tinggi - Rizky Amelia, Dhea; Setyonaluri, Diahhadi (UI Scholars Hub, 2020)
As technology alters the way organizations work, the need for labor adjustment which more adaptable to technological changes has risen in high digital intensive sectors. However, vocational graduates face difficulties regarding this situation as their vocational school failed to equip them with advanced technological skills. Based on signaling and human capital investment theory, this problem can be solved by increasing education and training. Using 2015 and 2018 Sakernas data and logit regression, the result shows that vocational engineering and technology graduates have the highest probability to work in HDI sectors. however, working in a HDI sector cannot be associated with a better type or a more decent job than other sectors. This refers to the second finding that shows graduates of engineering and technology vocational schools have a lower probability of working as a white-collar even working at HDI sectors. According to the last finding, vocational tertiary education has shown to increase the probability of working as white-collar in HDI sectors, therefore a level up in education is needed to increase wages and improve job positions. Keywords: Vocational Education, Working Probability, High Digital Intensive Sectors